Seed Quality Enhancement Using Pulsed Electromagnetic Field in Mungbean (Vigna radiata L. Wilczek) - SIMARJEET KAUR; RUPINDER KAUR; GEETA BASSI (Seed Research, 2026)
Considering the importance of pulsed electromagnetic field (PEMF) in seed quality improvement, present study was conducted using fresh and revalidated mungbean seed after exposing to different PEMFs (1 Hz, 10 Hz, 50 Hz and 100 Hz). The effect was registered in terms of seed germination per cent, total soluble sugars (TSS), enzymatic activity and free amino acid content. Overall, all the frequencies improved the quality parameters under study but 100 and 50 Hz were found to be superior and at par with each other in their effect in both seed lots. In fresh seed lot there was increase in germination per cent (98% and 97%) over control (78%) and increase in TSS (552.3 and 540.9 mg/g respectively) over control (522.7 1 mg/g). The amylase activity also enhanced Ito 4.6moles ming and 4.5moles ming¹ over control (3.3moles ming). Likewise, free amino acid content also augmented to 56.85 mg/g and 55.65 mg/g respectively over 53.14 mg/g in control. Similarly in revalidated seed lot, higher germination per cent (92.8% and 92%) over control (75%) and higher TSS (528.2mg/g and 520.6mg/g) over control (500.9mg/g) were registered. The amylase activity also elevated to 3.9 moles ming¹ and 3.8 moles min¹g-¹, , over the control (2.9moles ming). Likewise free amino acid content also increased to 53.50 mg/g and 53.31mg/g, respectively over the control (52.26mg/g). Hence present findings indicated that the mungbean seed may be given an exposure of 50 Hz or 100 Hz with PEMF before sowing, to improve its quality.